Global antitrust law and economics - Elhauge, Einer (Foundation Press Thomson/West, 2007)
his new casebook presents a globalized approach to antitrust law and provides an understanding of the main antitrust regimes that apply throughout the world today. Whether in business, law, or government, we can no longer content ourselves with understanding only the antitrust and competition law of one nation. The authors present a truer picture of the overall regime of competition law that now faces multinational market players through a combination of laws from varying nations in actual application. The authors have structured the book to enhance a teacher's ability to take a modular approach. Thus, depending on the assignments the teacher wishes to make out of the book, the book can be used to either: (a) to replace the basic Antitrust course with a course fully covering the relevant US and EC laws that regulate global market conduct, (b) to teach a course that fully covers U.S. antitrust law and adds only readings on selected topics in EC competition law, or (c) to teach an advanced course in EC competition law.